Porcine γδ T cells express cytotoxic cell-associated markers and display killing activity but are not selectively cytotoxic against PRRSV- or swIAV-infected macrophages - Bettin, Leonie; Darbellay, Joseph; van Kessel, Jill; Dhar, Neeraj; Gerdts, Volker (Frontiers in Immunology, 2024)
Gamma-delta (γδ) T cells are a major immune cell subset in pigs. Approximately 50% of circulating T cells are γδ T cells in young pigs and up to 30% in adult sows. Despite this abundance, the functions of porcine γδ T cells are mostly unidentified. In humans and mice, activated γδ T cells exhibit broad innate cytotoxic activity against a wide variety of stressed, infected, and cancerous cells through death receptor/ligand-dependent and perforin/granzyme-dependent pathways. However, so far, it is unknown whether porcine γδ T cells have the ability to perform cytotoxic functions. In this study, we conducted a comprehensive phenotypic characterization of porcine γδ T cells isolated from blood, lung, and nasal mucosa. Our results show that only CD2 + γδ T cells express cytotoxic markers (CD16, NKp46, perforin) with higher perforin and NKp46 expression in γδ T cells isolated from lung and nasal mucosa.To further analyze the cytolytic potential of γδ T cells, in vitro cytotoxicity assays were performed using purified γδ T cells as effector cells and virus-exposed or mock-treated primary porcine alveolar macrophages as target cells. We found that γδ T cells can exhibit cytotoxic functions, potentially triggered by cellular stress, in a cell-cell contact and degranulation-dependent manner. However, porcine γδ T cells did not seem to specifically target Porcine Reproductive and Respiratory Syndrome Virus or swine Influenza A Virus-infected macrophages, which may be due to viral escape mechanisms.